Mental disorders in the classical world - Harris, William V. (William Vernon) (Columbia studies in the classical tradition, 2013)
Mental Disorders in the Classical World seeks to show through interdisciplinary work how the first medical scientists and their lay contemporaries conceptualized mental disorders and attempted to diagnose, understand and treat them.